Molecular Donor–Acceptor Dyads for Efficient Single-Material Organic Solar Cells - Lucas, Sebastian; Kammerer, Jochen; Pfannmoeller, Martin; Schroeder, Rasmus R.; He, Yakun; Li, Ning; Brabec, Christoph; Leydecker, Tim; Samori, Paolo; Marszalek, Tomasz; Pisula, Wojchiech; Mena-Osteritz, Elena; et al. (Solar RRL, 2020)
Single-material organic solar cells (SMOSCs) promise several advantages with respect to prospective applications in printed large-area solar foils. Only one photoactive material has to be processed and the impressive thermal and photochemical long-term stability of the devices is achieved. Herein, a novel structural design of oligomeric donor–acceptor (D–A) dyads 1–3 is established, in which an oligothiophene donor and fullerene acceptor are covalently linked by a flexible spacer of variable length. Favorable optoelectronic, charge transport, and self-organization properties of the D–A dyads are the basis for reaching power conversion efficiencies up to 4.26% in SMOSCs. The dependence of photovoltaic and charge transport parameters in these ambipolar semiconductors on the specific molecular structure is investigated before and after post-treatment by solvent vapor annealing. The inner nanomorphology of the photoactive films of the dyads is analyzed with transmission electron microscopy (TEM) and grazing-incidence wide-angle X-ray scattering (GIWAXS). Combined theoretical calculations result in a lamellar supramolecular order of the dyads with a D–A phase separation smaller than 2 nm. The molecular design and the precise distance between donor and acceptor moieties ensure the fundamental physical processes operative in organic solar cells and provide stabilization of D–A interfaces.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ambipolar charge transport; donor–acceptor dyads; fullerenes; oligothiophenes; single-material organic solar cells